Cardiovascular effects of high-intensity interval aerobic training combined with strength exercise in patients with chronic heart failure. A randomized phase III clinical trial. (20th January 2015) - Chrysohoou, Christina; Angelis, Athanasios; Tsitsinakis, George; Spetsioti, Stavroula; Nasis, Ioannis; Tsiachris, Dimitris; Rapakoulias, Panagiotis; Pitsavos, Christos; Koulouris, Nikolaos G.; Vogiatzis, Ioannis; Dimitris, Tousoulis
Abstract: Background: The aim of this work was to evaluate the effect of high-intensity interval exercise (i.e., 30 s at 100% of max workload, followed by 30 s at rest, 45 min 3 days/week working-out schedule for 12 weeks) on left ventricular function and aortic elastic properties among chronic heart failure (CHF) patients. Methods: This study is a phase III clinical trial. Of the 100 consecutive CHF patients (NYHA classes II–IV, ejection fraction < 50%) that were randomly allocated, 72 completed the study (exercise training group, n = 33, 63 ± 9 years, 88% men, and control group, n = 39, 56 ± 11 years, 82% men). All patients underwent cardiopulmonary stress test, non-invasive high-fidelity tonometry of the radial artery, pulse wave velocity measurement using a SphygmoCor device and echocardiography before and after the completion of the training program. Results: Both groups reported similar medical characteristics and physical activity status. General mixed effects models revealed that the intervention group reduced pulse wave velocity by 9% (p = 0.05); Emv/Vp by 14% (p = 0.06); E to A ratio by 24% (p = 0.004), E to Emv ratio by 8% (p = 0.05), MLHFQ score by 66% (p = 0.003) and the depression score by 19% (p = 0.5); increased augmentation index by 29%; VTI by 4% (p = 0.05), 6-minute-walk distance up to 13% (p = 0.05), peak oxygen uptake by 28% (p = 0.001) and peak power by 25% (p = 0.005). There were no significant changes in the control group. Conclusion: Interval high-intensity aerobic training, combined with strength exercise, seems to benefit aortic dilatation capacity and augmented systolic pressure in parallel with improvement in left ventricular diastolic function and quality of life.